2015
DOI: 10.1007/s10919-015-0226-4
|View full text |Cite
|
Sign up to set email alerts
|

Be Careful Where You Smile: Culture Shapes Judgments of Intelligence and Honesty of Smiling Individuals

Abstract: Smiling individuals are usually perceived more favorably than non-smiling ones—they are judged as happier, more attractive, competent, and friendly. These seemingly clear and obvious consequences of smiling are assumed to be culturally universal, however most of the psychological research is carried out in WEIRD societies (Western, Educated, Industrialized, Rich, and Democratic) and the influence of culture on social perception of nonverbal behavior is still understudied. Here we show that a smiling individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 40 publications
0
52
0
10
Order By: Relevance
“…Previous cross‐cultural studies on sexism (Glick et al, , ) explicitly activated gender stereotypes and showed that the women‐are‐wonderful effect is ubiquitous across cultures (Glick et al, ). We reanalysed data collected in 44 cultures by Krys et al () and found that the women‐are‐wonderful effect, when measured indirectly (i.e. when participants do not explicitly express their beliefs about each gender), is smaller in societies that are more gender‐egalitarian.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous cross‐cultural studies on sexism (Glick et al, , ) explicitly activated gender stereotypes and showed that the women‐are‐wonderful effect is ubiquitous across cultures (Glick et al, ). We reanalysed data collected in 44 cultures by Krys et al () and found that the women‐are‐wonderful effect, when measured indirectly (i.e. when participants do not explicitly express their beliefs about each gender), is smaller in societies that are more gender‐egalitarian.…”
Section: Discussionmentioning
confidence: 97%
“…Also, perceiver ethnicity should be analysed in future studies as ingroup and outgroup effects may play a role in these social perception processes. Next, following Krys et al () we used the term culture , although the group‐level distinctions could have alternatively been labelled national culture or just nation (excluding South Africa and India as they were explicitly split into cultural sub‐samples). We are aware that culture is a far more complex construct than nation ; future studies need to be more precise in differentiating these two.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Western cultures, where expressing emotions related to happiness is highly valued (Lyubomirsky et al, 2005;M. Erber & R. Erber, 2001;Saami, 1984), and happy-looking people are more liked (Lyubomirsky et al, 2005;Krys et al, 2016), even young children unconsciously smile due to learning that smiling in the presence of others is expected and rewarded (Saami, 1984). It is then plausible that the process by which people's behaviours are transformed into their positive affect is similar to that proposed by the facial feedback hypothesis.…”
Section: Othersmentioning
confidence: 98%